Guidelines for the public on how to provide mental health first aid: narrative review - Anthony F. Jorm; Anna M. Ross (BJPsych Open, 2018)
BackgroundExpert-consensus guidelines have been developed for how members of the public should assist a person with a mental health problem or in a mental health crisis.AimsThis review aimed to examine the range of guidelines that have been developed and how these have been implemented in practice.MethodA narrative review was carried out based on a systematic search for literature on the development or implementation of the guidelines.ResultsThe Delphi method has been used to develop a wide range of guidelines for English-speaking countries, Asian countries and a number of other cultural groups. The primary implementation has been through informing the content of training courses.ConclusionFurther work is needed on guidelines for low- and middle-income countries.Declaration of interestA.F.J. is an unpaid member of the Board of Mental Health First Aid International (trading as Mental Health First Aid Australia), which is a not-for-profit organisation.